Biochemistry of aroma compounds in cheese - Luna Maslov Bandić; Fabijan Oštarić; Marko Vinceković; Nataša Mikulec (Mljekarstvo)
Cheese is one of the most popular dairy products, with an incredible diversity of varieties, shapes, textures, and flavours available locally and globally. Extensive research has been conducted on the aroma compounds present in cheese. Numerous studies have identified over 3000 volatile and non-volatile components in cheese. The volatile components, which consist of fatty acids, alcohols, aldehydes, esters, ketones, lactones, sulphur compounds, amines, and other flavour-active compounds, are primarily responsible for the aromatic characteristics (aroma) of cheese. This paper thoroughly discusses the biochemistry behind the formation of significant aroma compounds that affect overall cheese quality and sensory characteristics. It provides an extensive review of the most recent methodologies for the extraction and determination of aroma compounds in cheese.